2021
DOI: 10.15575/join.v6i1.719
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Classification Methods in Hepatitis C Virus

Abstract: The hepatitis C virus (HCV) is considered a problem to the health of societies are the main. There are around 120-130 million or 3% of the world's total population infected with HCV. Without treatment, most major infectious acute evolve into chronic, followed by diseases liver, such as cirrhosis and cancer liver. The data parameters used in this study included albumin (ALB), bilirubin (BIL), choline esterase (CHE), -glutamyl-transferase (GGT), aspartate amino-transferase (AST), alanine amino-transferase (ALT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
(28 reference statements)
2
7
0
3
Order By: Relevance
“…L. Syafa’ah et al [ 14 ] evaluated the algorithms KNN, naive Bayes, neural networks, and RF for detection of hepatitis C. The results demonstrated that NN’s accuracy can reach 95.12%, higher than naive Bayes, KNN, and RF. Another study, by Oleiwi et al [ 15 ], used four machine learning techniques (KNN, SVM, naive Bayes, and decision tree).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. Syafa’ah et al [ 14 ] evaluated the algorithms KNN, naive Bayes, neural networks, and RF for detection of hepatitis C. The results demonstrated that NN’s accuracy can reach 95.12%, higher than naive Bayes, KNN, and RF. Another study, by Oleiwi et al [ 15 ], used four machine learning techniques (KNN, SVM, naive Bayes, and decision tree).…”
Section: Discussionmentioning
confidence: 99%
“…El-Salam et al [ 12 ] used multiple-classifier models and achieved accuracy rates ranging from 65.6% to 68.9%. Hashem et al [ 13 ] applied several machine learning approaches and found an accuracy range of 66.3% to 84.4% for predicting advanced chronic hepatitis C. Syafa’ah et al [ 14 ] evaluated multiple algorithms and found that neural networks had the highest accuracy (95.12%). Oleiwi et al [ 15 ] used four machine learning techniques and found that the decision tree method had the best accuracy (93.44%) for classifying and diagnosing hepatitis C. This study aims to choose the best algorithms for predicting hepatitis C based on routine and inexpensive blood test data.…”
Section: Introductionmentioning
confidence: 99%
“…But the main disadvantage of Logistic regression is over tting and multicollinearity. It is tough to extract the complex patterns in the given data set with highest accuracy [12].…”
Section: Related Materials and Methodsmentioning
confidence: 99%
“…Penerapan model lain dengan menggunakan pendekatan deep learning yaitu artificial neural network (ANN) untuk mendeteksi hepatitis C mampu menghasilkan akurasi 97,78% [9]. Study lain membahas tentang evaluasi penerapan berbagai algoritma klasifikasi machine learning untuk deteksi virus hepatitis C, algoritma tersebut adalah naïve bayes, random forest, dan KNN [10].…”
Section: Pendahuluanunclassified